2012
DOI: 10.1016/j.mce.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of the ENaC-regulatory complex in aldosterone-mediated sodium transport

Abstract: The mineralocorticoid aldosterone is indispensable for the control of blood pressure and fluid volume in mammals. It acts in large part to increase the abundance and activity of the epithelial Na+ channel (ENaC), which mediates apical Na+ entry in the distal parts of the kidney tubules. Aldosterone acts through the mineralocorticoid receptor to alter the transcription of specific genes, including SGK1 and GILZ1. Recent evidence suggests that these key aldosterone-regulated factors function within a unique mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 72 publications
2
36
0
Order By: Relevance
“…Dysregulation of ENaC may affect a variety of functions including deranged regulation of renal salt excretion [45], blood pressure [29], cell volume [46], fluid transport in the lung [47,48], endothelial function [49] and embryo implantation [50]. To which extent SPAK or WNK sensitive activation of SPAK participates in the regulation of those functions remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of ENaC may affect a variety of functions including deranged regulation of renal salt excretion [45], blood pressure [29], cell volume [46], fluid transport in the lung [47,48], endothelial function [49] and embryo implantation [50]. To which extent SPAK or WNK sensitive activation of SPAK participates in the regulation of those functions remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…8,11,23 Classically, sodium transport into kidney collecting ducts is mediated by aldosterone/MR induction of ENaCα. 53 ENaCα is also expressed in Müller cells 37,38,54 and may influence cell function, 17,54 although how this occurs is not fully understood. Recent studies identified that MR is expressed in Müller cells, 23,37,38 and furthermore, aldosterone and the MR stimulated the expression of ENaCα in Müller cells.…”
Section: Discussionmentioning
confidence: 99%
“…During the past 15 years, considerable progress has been made in the characterization of these cellular events, and numerous aldosteroneinduced proteins have been identified, including serum-and glucocorticoid-dependent kinase 1 (SGK1) (10,33), glucocorticoid-induced leucine zipper protein (GILZ) (40), the adaptor protein 14-3-3␤ (26), scaffold protein connector enhancer of kinase suppressor of RAS isoform 3 (CNK3) (49), or the deubiquitylating enzyme USP2-45 (14). Importantly, evidence has been provided that these proteins form a complex which may regulate ENaC function via posttranslational modifications including ubiquitylation (i.e., the posttranslational modification of target proteins with ubiquitin) (11,26,48). Ubiquitylation is now recognized as an essential mechanism for regulating cellular and physiological processes (12,43,54).…”
mentioning
confidence: 99%